2017
DOI: 10.1093/toxsci/kfw267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum lipid, thyroid, and hepatic clinical chemistries in association with serum perfluorooctanesulfonate (PFOS) in cynomolgus monkeys after oral dosing with potassium PFOS

Abstract: An oral dose study with perfluorooctanesulfonate (PFOS) was undertaken to identify potential associations between serum PFOS and changes in serum clinical chemistry parameters in purpose-bred young adult cynomolgus monkeys (Macaca fascicularis). In this study, control group (n = 6/sex) was sham-dosed with vehicle (0.5% Tween 20 and 5% ethanol in water), low-dose group (n = 6/sex) received 1 single K+PFOS dose (9 mg/kg), and high-dose group (n = 4–6/sex) received 3 separate K+ PFOS doses (11–17.2 mg/kg). Monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Chang et al () treated cynomolgus monkeys with a single dose of 9 mg PFOS/kg bw by gavage and reported on an insignificant reduction of serum cholesterol in the post‐treatment phase. No further alterations could be observed.…”
Section: Appendix D – Effects Following Acute Exposurementioning
confidence: 99%
“…Chang et al () treated cynomolgus monkeys with a single dose of 9 mg PFOS/kg bw by gavage and reported on an insignificant reduction of serum cholesterol in the post‐treatment phase. No further alterations could be observed.…”
Section: Appendix D – Effects Following Acute Exposurementioning
confidence: 99%
“…Several experimental animal studies (n=8) reported short-term clinical effects related to PFAS exposure, with most studies showing small changes in BUN and/or creatinine concentrations across a wide range of exposure doses (42,43,45,47,48,59,79,80). However, the short-term clinical effects were variable, with some animal studies (n=3) showing no changes in BUN or creatinine at exposure doses as high as 600 mg/kg for PFOA (41,44,46), and others showing increased concentrations of both BUN and creatinine at exposure doses as low as 0.05-1.00 mg/kg for perfluoroundecanoic acid and perfluorododecanoic acid (47).…”
Section: Clinical and Histologic Findingsmentioning
confidence: 99%
“…Disruption of the thyroid hormone system has been reported in both epidemiological (Dallaire et al 2009;Knox et al 2011;Wen et al 2013) and animal studies (Chang et al 2008;Curran et al 2008;Luebker et al 2005;Martin et al 2007;Seacat et al 2002;Thibodeaux et al 2003). However, not all epidemiological studies have found a negative correlation with PFOS levels in serum (Olsen et al 2003), nor all animal studies (Chang et al 2017). Nevertheless, PFOS has been identified as a thyroid hormone disruptor (ATSDR 2018;Coperchini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all epidemiological studies have found a negative correlation with PFOS levels in serum ( Olsen et al. 2003 ), nor all animal studies ( Chang et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%